ANALISIS KADAR ALBUMIN SERUM DENGAN RASIO DE RITIS PADA PENDERITA HEPATITIS B - AT. Lopa; B. Rusli; M. Arif; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Hepatitis is a inflammation process which may present in an acute or chronic phase. A decrease of serum albumin level may befound in liver disease. Ratio de Ritis in mild hepatitis is < 1 while in alcoholic hepatitis is >1. To analyze serum albumin level withratio de Ritis in hepatitis B patients. A cross sectional study was carried out comprising 46 subjects from October 2005 to August 2006measuring albumin level SGOT and SGPT levels using Lyasis autoanalyzer. Thirty eight males and eight females, the level of serumalbumin decreased with an average of albumin level 2.98 gr/dL (p<0.05). Twenty two subjects showed a ratio de Ritis ≤ 1 with theaverage albumin level 3.00 gr/dL and 24 subjects were included in group ratio de Ritis > 1 with average albumin level 2.96 gr/dL(p value = 0.658). There was a decrease of serum albumin level in hepatitis B patient but no significant difference between decrease ofserum albumin level with ratio of de Ritis ≤ 1 and ratio of de Ritis >1.